THE USE OF STORYTELLING IN TEACHING LISTENING : A Case Study of Eighth Grade at One Junior High School in Bandung - Zulaeka, Eka (2014)
This study is aimed to investigate the use of storytelling in teaching listening in one junior high school. It examined the implementation of teaching listening through using storytelling which were focused on finding out the advantages of storytelling and described students' responses toward using storytelling in their listening activity. This study was conducted based on the current concern regarding to listening practice which is often neglected from teaching and learning process in the classroom, particularly in the context of foreign language learning (Brown and Yule: 1983). The analysis of the previous studies revealed that listening is considered as one of the most difficult skills to acquire (Field: 2008). In accordance with it, Haven (2007), states that the use of storytelling is considered as a valuable technique to enhance listening skill (Haven: 2007). Moreover, the use of storytelling is appropriate to be implemented since it has pedagogical value, particularly on listening activity (Castro, 2002; cited in Verdugo and Belmonte, 2007). A case study was employed as research design in this study, and the data were collected through observation, interview, and written documents. The data from these three instruments were analyzed qualitatively, specifically using triangulation technique. The results of the study were based on the previous findings from the studies conducted by Skhela (2010) who states that storytelling is an effective technique to be used in teaching listening. The research findings of the study indicates some advantages on using storytelling in teaching listening, as follows: (1) it keeps students' engagement during listening activity; (2) it generates enthusiasm and motivation among the students; (3) it increases students' willingness to communicate thoughts and feelings; (4) it triggers learners' participation to get involved with the story of being told; (5) it encourages cooperation between students;(6) it enhances listening skill; (7) it helps students to develop listening strategies; and (8) it helps learners to acquire new vocabularies purposefully. In other words, storytelling is recommended to be used on teaching listening particularly at junior high school level. Key words: storytelling, listening skill, and case study Penelitian ini menguji penggunaan mendongeng dalam pengajaran tingkat SMP. Penelitian ini ditujukan untuk meneliti pelaksanaan pengajaran mendengarkan melalui mendongeng yang difokuskan untuk mencari keunggulan dari penggunaan mendongeng dalam pengajaran mendengarkan dan mendeskripsikan respon siswa terhadap penggunaan mendongeng dalam kegiatan mendengarkan. Penelitian ini dilakukan berdasarkan permasalahan dalam praktek mendengarkan yang jarang diimplementasikan dalam proses pembelajaran dan pengajaran di kelas, terutama pada konteks pembelajaran bahasa asing (Brown dan Yule: 1983). Analisa dari penelitian sebelumnya menunjukkan bahwa kegiatan mendengarkan dianggap sebagai salah satu keterampilan yang paling sulit untuk dikuasai (Field: 2008). Berkaitan dengan hal tersebut, mendongeng dinilai sebagai teknik yang tepat untuk meningkatkan keterampilan mendengarkan. Selain itu. penggunaan mendongeng cocok untuk diimplementasikan karena memiliki nila pedagogis, terutama dalam kegiatan mendengarkan (Castro, 2002; dikutip dari Verdugo and Belmonte, 2007). Dalam penelitian ini, studi kasus digunakan sebagai desain penelitian dan data yang digunakan meliputi observasi, wawancara, dan dokumen tertulis. Dari tiga instrumen ini dianalisis secara kualitatif, terutama menggunakan teknik triangulasi. Hasil dari penelitian didasarkan pada penemuan dari penelitian sebelumnya yang dilakukan oleh Skhela (2010) yang menyatakan bahwa mendongeng merupakan teknik yang efektif untuk digunakan dalam pengajaran mendengarkan. Dari hasil penelitian ini menunjukkan beberapa kelebihan dalam penggunaan teknik mendongeng dalam pengajaran mendengarkan, sebagai berikut: (1) menjaga keterikatan siswa selama kegiatan mendengarkan; (2) memicu antusias dan motivasi siswa antar siswa; (3) meningkatkan minat siswa untuk mengkomunikasikan idenya; (4) memicu partisipasi siswa untuk terlibat dengan cerita dalam kegiatan mendongeng; (5) mendorong kerja sama antar siswa antar siswa; (6) meningkatkan kemampuan mendengarkan; (7) membantu siswa mengembangkan strategi mendengarkan; (8) dan membantu siswa memperoleh kosa kata baru secara bermakna. Dengan kata lain, teknik mendongeng direkomendasikan untuk digunakan dalam pengajaran mendengarkan, terutama pada tingkat SMP. Kata kunci: mendongeng, keterampilan mendengarkan, dan studi kasus